Physical rehabilitation after spinal cord injury: maximizing function - Hastings, Jennifer (Henry Stewart Talks, 2011)
Principles of how to sequence and progress a functional rehabilitation program for an individual with motor complete SCI between C6-L1, Non ambulatory full time wheelchair user, Incorporating musculoskeletal protection, Focus on motor skill training and how a therapist facilitates positive neural plasticity when there is no motor recovery
Reviewed at 2022/04/12